2022
DOI: 10.1177/00469580221081997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Fidelity Simulation on Clinical Judgment Among Nursing Students

Abstract: Introduction Nursing education needs to be improved in order to bridge the gap between education and clinical practice. However, clinical placements for nursing students are limited and student nurses often take merely an observer role, especially in critical situations. High-fidelity simulation (HFS) is a teaching method that can bridge the gap between education and clinical practice. The purpose of this study was to evaluate the influence of using HFS as a teaching method on clinical judgment among pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Lee, J., & Son, H. K (e.g., Lee, J., & Son, H. K., 2022 ) conducted simulation training in obstetrics for 47 nursing students in Korea and investigated the effect of the training using questionnaires before and after the course, revealing that the experimental group’s communication attitude improved significantly after the simulation training. The study also found that this teaching method could improve nursing students’ clinical judgment (e.g., Ayed, A et al, 2022 ). A systematic evaluation (e.g., Lei, Y. Y et al, 2022 ) showed that scenario-based simulation has a strong effect on nursing education, helping nursing students to increase their knowledge base, enhance their professional skills and develop critical thinking skills and communication skills.…”
Section: Discussionmentioning
confidence: 91%
“…Lee, J., & Son, H. K (e.g., Lee, J., & Son, H. K., 2022 ) conducted simulation training in obstetrics for 47 nursing students in Korea and investigated the effect of the training using questionnaires before and after the course, revealing that the experimental group’s communication attitude improved significantly after the simulation training. The study also found that this teaching method could improve nursing students’ clinical judgment (e.g., Ayed, A et al, 2022 ). A systematic evaluation (e.g., Lei, Y. Y et al, 2022 ) showed that scenario-based simulation has a strong effect on nursing education, helping nursing students to increase their knowledge base, enhance their professional skills and develop critical thinking skills and communication skills.…”
Section: Discussionmentioning
confidence: 91%
“…The Lasater Clinical Judgment Rubric (LCJR) used in the study describes a wide range of clinical judgment development. 15 The LCJR has been psychometrically tested and utilized in nursing research to measure the effectiveness of guided reflection, 16 flipped classroom, 17 and high-fidelity simulation 18 on nursing students' clinical judgment cross different cultural contexts. 19 There was no literature found on the use of LCJR to measure the effect of unfolding CBL, a form of simulated experiences in the classroom, on students' clinical judgment.…”
Section: Instrumentmentioning
confidence: 99%
“…15 The rubric rates 11 clinical judgment behaviors across 4 development levels: beginning (1 point), developing (2 points), accomplished (3 points), or exemplary (4 points). 15 The overall score ranges from 11 to 44 and indicates nursing clinical judgment as developing (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), accomplished (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), and exemplary (34-44). The LCJR has been used in 3 distinct ways within the academic setting: as a self-assessment tool for students 20 ; as a framework for faculty to provide feedback and evaluate student clinical judgment skills 1 ; and as a measurement tool in nursing research.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergency environment can therefore never provide safe spaces for learners to make mistakes without consequence; whereas HFS does have scope to provide this. When HFS is utilised effectively, important gaps between theory and practice can be bridged [12]; whilst evoking strong emotional responses capable of cultivating enhanced levels of emotional preparedness and mental resilience [9]. Pedagogic stance, instructor experience and resource availability are major in uencers in simulation design and delivery; but at any level, ascertaining the most effective delity and modality are fundamental considerations [4,13].…”
Section: Introductionmentioning
confidence: 99%